Influencia de la variabilidad biológica en los resultados de la citometría hemática - Fernanda Lilian, Paredes Bermeo (2021)
ABSTRACT Hematic cytometry is one of the most practiced laboratory tests, it helps in the patient diagnosis, prevention and control. It measures different magnitudes, among them are the red white and platelets series, by its importance it has been maintained since the 30s with Wintrobe who described the erythrocyte indices. Automated analyzers are currently available, which allow the evaluation of biological magnitudes, as far as hematic cytometry is concerned, all these parameters are variable and represent a great clinical interest. Biological variability refers to the results found in different subjects, finding a different value for each of them and also to the values found in the same subject at different times. The objective of this bibliographic study was to collect information on the influence of biological variability on the results of hematic cytometry. For this, a qualitative, descriptive, documentary research was carried out that included 60 bibliographies published in indexed scientific journals of high global impact and several articles related to the subject of the project were collected, applying various inclusion and exclusion criteria. According to the readings analyzed, the biological variation had an influence on the different parameters of hematic cytometry due to different factors such as age, sex, menstrual cycle, pregnancy and others. Keywords: Biological variability, hematic cytometry. Reviewed by: Mgs. Janneth Caisaguano Villa. ENGLISH PROFESSOR c.c. 0602305443